До етнічної історії давнього Криму - Ольховський, В.С. (Археологія, 1990)
У статті на основі пам'яток, писемності, археологічних та антропологічних джерел розглядаються і реконструюються складні етнокультурні процеси, що відбувалися на території Кримського півострова у VII ст. до н. е.— IV ст. н. е., за участю автохтонного (таври) та прийшлих (скіфи, греки, сармати та ін.) етнічних компонентів. В статье рассматриваются письменные, археологические и палеоантропологические свидетельства о негреческом населении Крымского п-ва в I тыс. до — сер. I тыс. н. э. Анализ письменных источников привел к выводу об относительной автохтонности таврского населения Крыма, обитавшего в горах, предгорьях и части степи, о его племенной раздробленности и политической независимости в раннескифское время, а появлении в VI в. до н. э. группы смешанного скифо-аборигенного населения «потомки слепых»). Письменные данные согласуются с реконструируемой палеографической ситуацией: превращение Крыма и полуостров в результате морской трансгрессии, появление системы Сивашей и Перекопа на месте «ира-Перекопа». Подтверждается локализация рва «потомков слепых» на Акмонайском перешейке. Во II в. до н. э. в Крыму появляются сатархи (сарматское племя?). С этого времени усиливается процесс этнической интеграции разноплеменного варварского населения Крыма, отражением чего является появление этнонима тавро-скифы. Выделяются 4 группы археологических памятников Крыма VII—V вв. до н. э.: скифская (степь), таврская (горы), синкретичная (предгорья), предположительно смешанная (по обряду — скифская, но с кизил-кобинской керамикой; степь, предгорья). Позже лишь 1-я группа прогрессирует количественно и «качественно». Во II в. до — III в. н. э. наблюдается общая нивелировка погребальной обрядности варварского населения Крыма, унификация предметов материальной культуры, исчезновение «таврских» черт. Происходит формирование смешанных скифо-сармато-таврских групп населения при участии и других этнических компонентов — греков, аборигенов азиатского Боспора и др. Данный вывод полностью подтверждают и антропологические материалы. The paper is concerned with written, archaeological and paleoanthropological evidence on non-Greek population of the Crimean peninsula between the 1st millennium B.C. and mid. A.D. 1st millennium. An analysis of written sources has confirmed a relative aboriginal character of the Taurian population in the Crimea, inhabiting mountains, foothills and a part of steppe, its tribal scattering and political independence in the early Scythian period, appearance of a group of mixed Scythian-aboriginal population (descendants of the “blind”) in the 6th cent. B.C. The written data agree with the reconstructed pa leo geo graphic situation: transformation of the Crimea into a peninsula as a result of the sea transgression, appearance of a system of Sivashes and Perekop instead of “fore-Perekop”. Localization of a ditch of “blind descendants” on the Akinonai isthmus is confirmed. In the 2nd cent. B.C. satarchi (a Sarmatian tribe?) appear in the Crimea. Since that time the process of ethnic integration of the Barbarian population of different tribes in the Crimea gets more intensive resulting in the appearance of ethnonym Tauro-Scythians. Four groups of archaeological monuments in the Crimea of the 7th-5th cent. B.C. are distinguished: a Scythian (steppe), Taurian (mountains), Syncretic (foothills), supposedly mixed (Scythias as to rites but with Kizil-Kobian ceramics; steppe, foothills). Later on only the 1st group progresses quantitatively and “qualitatively". In the 2nd cent, B.C. and A.D, 3d cent, a general levelling of the funeral rites in the Barbarian population of the Crimea was observed as well as unification of subjects of the material culture, disappearance of “Taurian” properties. There occurred formation of mixed Scythian-Sarmatian-Taurian groups of population with participation of other ethnic components: Greeks, aboriginals from the Asian Bosporus and so on. Anthropological data have completely confirm the conclusion drawn.